Os sistemas agrícolas tradicionais nos interstícios da soja no Brasil: processos e limites da conservação da agrobiodiversidade. - Ludivine Eloy; Cláudia de Souza; Diana Nascimento; Mônica Celeida Rabelo Nogueira; Henyo Trindade Barretto Filho; Patricia Bustamante; Laure Emperaire (Confins)
The expansion of agribusiness in all Brazilians regions challenges the future of traditional agricultural systems. This article intends to identify the processes by which traditional farmers maintain agricultural diversity at the soybean frontier in Brazil. The data were obtained from the survey and mapping of agricultural practices and agrobiodiversity with 113 farmers from three indigenous, quilombola and peasant territories of the South, North-East and North of the country. Agricultural diversity in the interstices of soybean plantations (between 66 and 188 crop species and varieties) results from the continuous production of knowledge in experimentation spaces constituted by swidden agriculture. Traditional agricultural knowledge molds a heterogeneous soybean frontier, where the interstices cultivated by communities reveal themselves as islands of agrobiodiversity in a sea of monocultures. Far from being opposed to modernity or the market economy, traditional agricultural knowledge consists of processes of innovation that lie in the ingenious combination of "old" and "modern" practices and varieties. Thus, the concept of dynamic conservation allows to go beyond the common idea of the substitution of local varieties or the erosion of traditional knowledge in the face of agribusiness expansion. On the other hand, even in relatively stabilized traditional territories, the dynamic conservation of agrobiodiversity is threatened by the environmental impacts of soy expansion. Even if traditional ways of practicing agriculture are still operative in the interstices of soybeans, an extra-territorial process of disqualification of local agricultural knowledge underpin these agricultural systems because of the acceleration of rhythms and scales of environmental changes. Thus, measures to recognize, protect and monitor traditional territories are basic conditions for farmers to continue to conserve agrobiodiversity dynamically.